El don Juan, una inversión de la femineidad medieval demoniaca - Pizarro Granada, Maite (Pontificia Universidad Católica del Perú, 2022)
The amor hereos or aegritudo amoris was a type of medieval melancholy triggered by love rejection. It was caused by women but suffered by men, and it used to show a demonic kind of femininity. Many people would say this erotic conception disappeared, but there is enough evidence to believe don Juan’s tradition could be a different face of the same sort of love. According to this idea, the sinful behavior of don Juan would be a reproduction of the feminine eroticism exposed in the tradition of Spanish amatory treatises. Namely, it would have evolved from being a masculine melancholic disease to being a female one.

El presente artículo plantea una interpretación según la cual la tradición donjuanesca constituye una suerte de reescritura del amor hereos o de la aegritudo amoris. Este era un tipo de melancolía medieval sufrido por los hombres y causado por el rechazo amoroso de las mujeres que habría desaparecido junto con otros diagnósticos asociados a la teoría de los humores. Sin embargo, hay razones para pensar que ha sobrevivido en la literatura moderna desplazando su sintomatología a las damas burladas. En otras palabras, se espera demostrar que la conducta pecadora del don Juan constituye una suerte de reproducción contrapuesta del erotismo de las mujeres expuesto en la tratadística amatoria española.
Don Juan, an Inversion of Demonic Medieval Femininity
Keywords: melancholy; Illness; Contagion; Female frailty; Melancolía; Enfermedad; Contagio; Fragilidad femenina; https://purl.org/pe-repo/ocde/ford#6.02.06